ONE TOWN, ONE PRODUCT (OTOP) NEXT GEN’S MARKET AND PRODUCT STRATEGY IN QUEZON PROVINCE - Natividad, Maria Concepcion; Quendangan, Erwin (International Journal of Arts, Sciences and Education, 2025)
This research aims to enhance the market and product strategies of the One Town, One Product (OTOP) Next Gen initiative in Quezon Province by evaluating the market viability and product competitiveness of small and medium-sized enterprises (SMEs). Specifically, it will address the following inquiries regarding how the market viability of SMEs participating in the OTOP Next Gen Program will be evaluated in terms of both physical and digital marketplaces; how the product competitiveness of SMEs within this program will be assessed based on design, packaging, brand equity, quality, product line, and product mix; whether there is a significant difference between market viability and product competitiveness; which factors of product competitiveness significantly affect the market viability of SMEs; and what type of business model can be formulated for market and product strategy based on the summary of findings. The research used a descriptive survey method with a quantitative focus, gathering data from 68 willing SME owners and OTOP Hubs across 12 municipalities in Districts 1 and 2, as specified in the Department of Trade and Industry’s master list. Moreover, opinions were collected from 198 purposefully chosen and willing OTOP customers from Quezon to evaluate consumer perceptions. The study successfully assessed the market potential and competitiveness of small and medium-sized enterprises (SMEs) involved in the OTOP Next Gen Program in Quezon Province. Both business owners and consumers regard OTOP products as viable and competitive. Keywords: market, market viability, OTOP, product competitiveness, product strategy, small and medium-sized enterprises